METHODS FOR FORMING CRITICAL THINKING IN MATHEMATICS LESSONS IN PRIMARY EDUCATION - Kurbanov Sanjar (American Journals, 2023)
This article shows the practical application of the technology of forming critical thinking in the process of teaching mathematics to elementary school students.
Keywords: Critical thinking, thinking methods, problem research, palette, surface, polygon, perimeter.